A soft carbon material with diatomite-like structure and its preparation method and application
By regulating the soft carbon material of diatomaceous earth structure, the problems of poor rate performance and low cycle stability caused by volume effect of graphite negative electrode material in potassium ion batteries are solved, and high energy density, high power density and high first-time Coulomb efficiency are achieved Electrochemical properties.
Patent Information
- Application Number
- CN202310224134.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-10
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-03-10
AI Technical Summary
The graphite negative electrode material in existing potassium ion batteries has a large volume effect during the K+ embedding/detachment process, resulting in poor rate performance and low cycle stability, and cannot meet the needs of high energy density, high power density and high first-time Coulomb efficiency at the same time.
By combining diatomaceous earth with asphalt, pre-oxidation and annealing treatment and etching, soft carbon materials with diatomaceous earth-like structures are prepared, the layer spacing and defect structure are regulated, the storage location of potassium ions is increased, and electrochemistry is improved. performance.
It significantly slows down the volume change of potassium ions embedded/detachment, increases the adsorption capacity and specific surface area of the negative electrode material, improves the electrochemical reaction efficiency, and enhances the cycling stability and current density performance of the potassium ion battery.
Smart Images

Figure CN116462183B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of energy material chemistry, and in particular relates to a soft carbon material with a diatomite-like structure and a preparation method and application thereof. Background Art
[0002] Research on potassium-ion batteries with high energy density and high power density has important scientific significance and practical value. Carbon materials have the advantages of stable chemical properties, high electrical conductivity, designable morphology and structure, diverse preparation methods, and low cost, and are widely used as negative electrode materials for potassium-ion batteries. For energy density, according to the formula Eq = E × Q, it can be seen that the effective strategy to improve the energy density Eq is to increase the working voltage E and specific capacity Q of the battery system, where E is determined by the voltage difference between the positive and negative electrodes, and Q is related to the potassium storage capacity of the electrode material. For power density, the rate performance of carbon negative electrode materials has an important influence on the power density of potassium-ion batteries. Therefore, the development of new carbon negative electrode materials with low ion storage potential, high specific capacity, high rate performance, and high first coulombic efficiency is the key to the development of high energy density and high power density potassium-ion batteries.
[0003] As one of the most attractive negative electrode materials, graphite has a theoretical capacity of about 273 mAh / g and a low discharge platform in potassium ion batteries (KIBs). + The volume effect of graphite in the insertion / extraction process is large, and the rate performance is poor. Therefore, the application of graphite in KIBs is limited. Studies have found that soft carbon (SC) with adjustable structure exhibits extremely attractive potassium storage behavior. However, unregulated SC materials + After the insertion / removal of the SC, a large volume change will occur, which greatly reduces the cyclic stability of the material. Therefore, the present invention provides a method for preparing a diatomite-like structural material by regulating the SC structure. By regulating the structure of the SC material, the potassium storage performance of the material is greatly improved. Summary of the invention
[0004] The purpose of the present invention is to provide a soft carbon material with a diatomite-like structure, by first compounding a SC precursor and diatomite, and then etching away the diatomite in the combination after carbonization, thereby obtaining a SC material with a diatomite-like structure. The material obtained by this method greatly regulates the interlayer spacing of the SC material, greatly alleviating the large volume change of the material during the embedding / ejection process. The defects generated also greatly increase the K + storage sites, thereby greatly improving the electrochemistry of the material and exhibiting excellent potassium storage performance.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is: a method for preparing a soft carbon material with a diatomite-like structure, the preparation method specifically comprises the following steps:
[0006] S1, dissolving diatomaceous earth in an organic solvent, adding asphalt, stirring and mixing, and then evaporating in a water bath to obtain a soft carbon material precursor;
[0007] S2. Under the protection of an inert gas, the soft carbon material precursor is first subjected to a pre-oxidation treatment and then subjected to an annealing treatment to obtain a composite material;
[0008] S3, etching the diatomite in the composite material obtained in step S2 to obtain a soft carbon material with a diatomite-like structure.
[0009] The present invention uses asphalt and diatomaceous earth as main raw materials, fully dissolves a certain amount of diatomaceous earth in an organic solvent, then disperses and dissolves a certain amount of asphalt in the above solution, stirs on a stirrer overnight to fully mix it, then evaporates it in a water bath (stirring is kept during the period), evaporates the organic solvent in the beaker, and then puts the product into a porcelain ark and transfers it to a muffle furnace for pre-oxidation treatment. The carbonyl functional groups generated in the pre-oxidation process cross-link with the asphalt molecules, preventing the melting and orderly rearrangement of the asphalt in the high-temperature carbonization process, and generating a large number of disordered structures. The generation of disordered structures generates a large number of active sites, which greatly increases the potassium storage performance of the material. The material is then transferred to a tubular furnace for annealing treatment, and the obtained product is etched with hydrofluoric acid to obtain an SC negative electrode material with a diatomaceous earth-like structure.
[0010] Preferably, in step S1, the diatomaceous earth is selected from at least one of red diatomaceous earth, black diatomaceous earth and calcium diatomaceous earth.
[0011] Preferably, in step S1, the organic solvent is selected from at least one of N,N-dimethylformamide, carbon disulfide, ethanol and carbon tetrachloride.
[0012] Preferably, in step S1, the mass ratio of asphalt to diatomaceous earth is 1:(1-10).
[0013] Preferably, in step S2, the specific process of the pre-oxidation treatment is as follows: heating to 100-300° C. at a heating rate of 0.5-10° C. / min in an air atmosphere and then sintering for 5-20 hours.
[0014] Preferably, in step S2, the specific steps of annealing treatment are as follows: under the protection of argon or nitrogen gas, the soft carbon material precursor after pre-oxidation treatment is heated to 650-1300°C at a heating rate of 5-20°C / min and continued for 0.5-4h.
[0015] Preferably, in step S3, the solvent used for etching is hydrofluoric acid or sodium hydroxide.
[0016] The second object of the present invention is to provide a soft carbon material with a diatomaceous earth-like structure, which is prepared by the above preparation method.
[0017] The third object of the present invention is to provide a soft carbon material with a diatomaceous earth structure for use in a negative electrode of a battery.
[0018] Compared with the prior art, the present invention has the following advantages:
[0019] 1. The SC material with a diatomite-like structure prepared by the present invention using the structure regulation technology slows down the K + The huge volume expansion during the insertion / extraction process;
[0020] 2. The SC material with diatomite-like structure prepared by the present invention greatly increases K + The storage sites increase the adsorption capacity of the negative electrode material;
[0021] 3. The SC material with a diatomite-like structure prepared by the present invention is applied to the negative electrode of the battery, which increases the specific surface area of the negative electrode material, reduces the ion migration distance, and promotes the electrochemical reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a Raman image of the SC material with a diatomite-like structure prepared in Example 1 of the present invention;
[0023] Figure 2 This is a SEM image of the SC material with a diatomite-like structure prepared in Example 1 of the present invention;
[0024] Figure 3 TEM image of the SC material with a diatomite-like structure prepared in Example 1 of the present invention;
[0025] Figure 4 This is a charge and discharge cycle performance diagram of the SC material with a diatomaceous earth-like structure prepared in Example 1 of the present invention as a KIBs negative electrode material at a current density of 1000 mA / g. DETAILED DESCRIPTION
[0026] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0027] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0028] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0029] The embodiment of the present invention provides a method for preparing a soft carbon material with a diatomite-like structure, which specifically comprises the following steps:
[0030] S1, dissolving diatomaceous earth in an organic solvent, adding asphalt, stirring and mixing, and then evaporating in a water bath to obtain a soft carbon material precursor;
[0031] In a specific embodiment, the diatomaceous earth is selected from at least one of red diatomaceous earth, black diatomaceous earth and calcium diatomaceous earth, the organic solvent is selected from at least one of N,N-dimethylformamide, carbon disulfide, ethanol and carbon tetrachloride, and the mass ratio of asphalt to diatomaceous earth is 1:(1-10).
[0032] S2. Under the protection of inert gas, the soft carbon material precursor is first heated to 100-300°C at a heating rate of 0.5-10°C / min in an air atmosphere and then sintered for 5-20h for pre-oxidation treatment. Then, under the protection of argon or nitrogen gas, the soft carbon material precursor after pre-oxidation treatment is heated to 650-1300°C at a heating rate of 5-20°C / min and annealed for 0.5-4h to obtain a composite material; the carbonyl functional groups generated in the pre-oxidation process are cross-linked with the asphalt molecules to prevent the melting and orderly rearrangement of the asphalt during the high-temperature carbonization process, thereby generating a large number of disordered structures. The generation of disordered structures enables it to have both slope specific capacity and platform specific capacity;
[0033] S3, etching the diatomite in the composite material obtained in step S2 with hydrofluoric acid or sodium hydroxide to obtain a soft carbon material with a diatomite-like structure.
[0034] The embodiment of the present invention provides a method for preparing a soft carbon material with a diatomite-like structure, and the SC material with a diatomite-like structure prepared by the structure control technology slows down the K + The huge volume expansion during the insertion / extraction process;
[0035] The embodiment of the present invention further provides a soft carbon material with a diatomite-like structure, which is prepared by the above preparation method.
[0036] The embodiment of the present invention also provides the use of the soft carbon material with a diatomaceous earth-like structure in a negative electrode of a battery.
[0037] The technical effects of the present invention are described below in conjunction with specific embodiments.
[0038] Example 1
[0039] Add 5 g of diatomaceous earth to a beaker containing 50 ml of DMF solvent and stir. After 1 hour, add 1 g of asphalt, seal with plastic wrap and stir overnight, then open the plastic wrap, transfer the beaker to a water bath (oil bath) pot, and evaporate in a water bath to obtain a dry asphalt and diatomaceous earth composite. Transfer the dried precursor to a muffle furnace for pre-oxidation treatment, raise the temperature to 200 ° C at 1 ° C / min in an air atmosphere, sinter for 12 hours, and transfer the obtained pre-oxidized product to a tubular furnace for deoxidation. Fire treatment, in a tubular furnace under argon atmosphere, the temperature was raised to 750°C at a rate of 10°C / min, and sintered at 750°C for 2h to obtain a composite of the target SC material and diatomite. The diatomite in the composite was etched with hydrofluoric acid, washed with deionized water and ethanol and centrifuged three times, and then dried in a 60°C forced air oven for 12 hours to obtain the SC material with a diatomite-like structure prepared by regulating the material structure; the carbon structure of the material was tested and analyzed using a confocal micro-Raman spectrometer ( Figure 1 ); Cold field scanning electron microscopy and transmission scanning electron microscopy showed that the morphology of the prepared product was nanosheets ( Figure 2 , 3), the obtained product was used as the negative electrode material of KIBs. After 1000 cycles at a current density of 1000mA / g, its reversible specific capacity could be maintained above 106.7mAh / g ( Figure 4 ).
[0040] Embodiment 2:
[0041] Add 3g of diatomaceous earth to a beaker containing 50ml of DMF solvent and stir. After 1h, add 1g of asphalt, seal with plastic wrap and stir overnight, then open the plastic wrap, transfer the beaker to a water bath (oil bath) pot, and evaporate in a water bath to obtain a dry asphalt and diatomaceous earth composite. The dried precursor is transferred to a muffle furnace for pre-oxidation treatment, heated to 200℃ at 1℃ / min in an air atmosphere, sintered for 12 hours, and the obtained pre-oxidized product is transferred to a tubular furnace for annealing treatment. In an argon atmosphere of the tubular furnace, the temperature is increased to 750℃ at a rate of 10℃ / min, and sintered at 750℃ for 2h to obtain a mixture of the target SC material and diatomaceous earth. The diatomaceous earth in the mixture was etched with hydrofluoric acid, washed with deionized water and ethanol, and centrifuged three times, and then dried in a 60°C forced air oven for 12 hours to obtain the SC material with a diatomaceous earth-like structure prepared by regulating the material structure; the carbon structure of the material was tested and analyzed by a confocal micro-Raman spectrometer; the prepared product was observed and analyzed using a cold-field scanning electron microscope and a transmission scanning electron microscope, and the obtained product was used as a KIBs negative electrode material to test its electrochemical properties using blue electricity.
[0042] Embodiment 3:
[0043] Add 7g of diatomaceous earth to a beaker containing 50ml of DMF solvent and stir. After 1h, add 1g of asphalt, seal with plastic wrap and stir overnight. Then open the plastic wrap, transfer the beaker to a water bath (oil bath) pot, and evaporate it in a water bath to obtain a dry asphalt and diatomaceous earth composite. Transfer the dried precursor to a muffle furnace for pre-oxidation treatment, heat it to 200℃ at 1℃ / min in an air atmosphere, and sinter it for 12 hours. The pre-oxidized product was transferred to a tube furnace for annealing. Under an argon atmosphere in the tube furnace, the temperature was raised to 750°C at a heating rate of 10°C / min and sintered at 750°C for 2 hours to obtain a composite of the target SC material and diatomite. The diatomite in the composite was etched with hydrofluoric acid, washed with deionized water and ethanol and centrifuged three times, and then dried in a 60°C forced air oven for 12 hours to obtain the SC material with a diatomite-like structure prepared by regulating the material structure. The carbon structure of the material was tested and analyzed using a confocal micro-Raman spectrometer. The prepared product was observed and analyzed using a cold-field scanning electron microscope and a transmission scanning electron microscope. The prepared product was used as a KIBs negative electrode material, and its electrochemical properties were tested using blue electricity.
[0044] Example 4
[0045] Add 5g of diatomaceous earth to a beaker containing 50ml of DMF solvent and stir. After 1h, add 1g of asphalt, seal with plastic wrap and stir overnight. Then open the plastic wrap, transfer the beaker to a water bath (oil bath) pot, and evaporate it in a water bath to obtain a composite of dry asphalt and diatomaceous earth. The dried precursor is transferred to a muffle furnace for pre-oxidation treatment, and the temperature is increased to 200℃ at 1℃ / min in an air atmosphere, and sintered for 12 hours. The obtained pre-oxidized product is transferred to a tubular furnace for annealing treatment. In an argon atmosphere of the tubular furnace, the temperature is increased to 650℃ at a rate of 10℃ / min, and sintered at 650℃ for 2h to obtain a composite of the target SC material and diatomaceous earth. The diatomaceous earth in the composite is etched with hydrofluoric acid, washed with deionized water and ethanol, and centrifuged 3 times. Then dry it in a 60℃ forced air oven for 12 hours. That is, the SC material with a diatomite-like structure prepared by regulating the material structure; the carbon structure of the material was tested and analyzed using a confocal micro-Raman spectrometer; the morphology of the prepared product was characterized by a cold-field scanning electron microscope and a transmission scanning electron microscope. The obtained product was used as a negative electrode material for KIBs and its electrochemical performance was tested using blue electricity.
[0046] Example 5
[0047] 5 g of diatomaceous earth was added to a beaker containing 50 ml of DMF solvent and stirred. After 1 hour, 1 g of asphalt was added, and the beaker was sealed with plastic wrap and stirred overnight. The plastic wrap was then opened, and the beaker was transferred to a water bath (oil bath) pot for water bath evaporation to obtain a dry composite of asphalt and diatomaceous earth. The dried precursor was transferred to a muffle furnace for pre-oxidation treatment, and the temperature was raised to 200°C at 1°C / min in an air atmosphere, and sintered for 12 hours. The obtained pre-oxidized product was transferred to a tube furnace for annealing treatment. In the argon atmosphere of the tube furnace, the temperature was raised to 850°C at a rate of 10°C / min, and sintered at 850°C for 2 hours to obtain a composite of the target SC material and diatomite. The diatomite in the composite was etched with hydrofluoric acid, washed with deionized water and ethanol, and centrifuged for 3 times, and then dried in a 60°C forced air oven for 12 hours, which is the SC material with a diatomite-like structure prepared by regulating the material structure; the carbon structure of the material was tested and analyzed by a confocal micro-Raman spectrometer; the morphology of the prepared product was characterized by a cold field scanning electron microscope and a transmission scanning electron microscope. The obtained product was used as a negative electrode material for KIBs and its electrochemical performance was tested using blue electricity.
[0048] Example 6
[0049] Add 5 g of diatomaceous earth to a beaker containing 50 ml of carbon disulfide solvent and stir. After 1 hour, add 1 g of asphalt, seal the beaker with plastic wrap and stir overnight. Then, the plastic wrap was opened, and the beaker was transferred to a water bath (oil bath) pot for water bath evaporation to obtain a dry asphalt and diatomite composite. The dried precursor was transferred to a muffle furnace for pre-oxidation treatment, and the temperature was increased to 200°C at 1°C / min in an air atmosphere, and sintered for 12 hours. The obtained pre-oxidized product was transferred to a tubular furnace for annealing treatment. In the argon atmosphere of the tubular furnace, the temperature was increased to 750°C at a rate of 10°C / min, and sintered at 750°C for 2 hours to obtain a target SC material and diatomite composite. The diatomite in the composite was etched with hydrofluoric acid, washed with deionized water and ethanol, and centrifuged for 3 times, and then dried in a 60°C forced air oven for 12 hours, which is a SC material with a diatomite-like structure prepared by regulating the material structure; the carbon structure of the material was tested and analyzed using a confocal micro-Raman spectrometer; the morphology of the prepared product was characterized by a cold-field scanning electron microscope and a transmission scanning electron microscope. The obtained product was used as KIBs negative electrode material and its electrochemical performance was tested using blue electricity.
[0050] Comparative Example 1:
[0051] 1g of asphalt was weighed and pre-oxidized in a muffle furnace. The temperature was raised to 200°C at a rate of 1°C / min in an air atmosphere and sintered for 12 hours. The pre-oxidized product was transferred to a tubular furnace for annealing. In the argon atmosphere of the tubular furnace, the temperature was raised to 750°C at a rate of 10°C / min and kept for 2 hours to obtain the target SC material. The carbon structure of the material was tested and analyzed using a confocal micro-Raman spectrometer. The prepared product was observed and analyzed using a cold-field scanning electron microscope and a transmission scanning electron microscope. The product was used as a KIBs negative electrode material to test its electrochemical properties using blue electricity.
[0052] The test results of the SC material with a diatomite-like structure prepared in Example 1 of the present invention show that the structural regulation alleviates the great volume change of the material during the insertion / extraction process. The defects generated also greatly increase the storage sites of potassium ions. As a negative electrode material for potassium batteries, its discharge specific capacity can be maintained above 106.7 mAh / g after 1000 charge and discharge cycles at a current density of 1000 mA / g.
[0053] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. A method for preparing a soft carbon material with a diatomite-like structure, characterized in that: The preparation method specifically comprises the following steps: adding 5g of diatomaceous earth to a beaker containing 50ml of DMF solvent and stirring, after 1h, adding 1g of asphalt, sealing with plastic wrap and stirring overnight, then opening the plastic wrap, transferring the beaker to a water bath, performing water bath evaporation to obtain a dry asphalt and diatomaceous earth composite, transferring the dried precursor to a muffle furnace for pre-oxidation treatment, heating to 200°C at 1°C / min in an air atmosphere, sintering for 12 hours, transferring the obtained pre-oxidation product to a tubular furnace for annealing treatment, heating at 10°C / min in an argon atmosphere in the tubular furnace, The temperature rate is increased to 750°C, and the mixture is sintered at 750°C for 2 hours to obtain a composite of the target SC material and diatomite. The diatomite in the composite is etched with hydrofluoric acid, washed with deionized water and ethanol and centrifuged for 3 times, and then dried in a 60°C forced air oven for 12 hours to obtain a soft carbon material with a diatomite-like structure. The morphology of the soft carbon material with a diatomite-like structure is nanosheets. The soft carbon material with a diatomite-like structure is used as a negative electrode material for KIBs. Under the condition of a current density of 1000mA / g, after 1000 cycles, its reversible specific capacity can be maintained above 106.7mAh / g.
Citation Information
Patent Citations
Method for preparing porous carbon and white carbon black by using diatomite
CN101913595A
Asphalt-based negative electrode material for sodium ion battery and preparation method and application thereof
CN109148883A